Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan (Studi Empiris Perusahaan Makanan Dan Minuman Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - WAHYU HIDAYAT, DIMAS, Dr. Rini Kuswati, S.E., M.Si (2016)
The disclosure of economic, environmental, social, labor, human rights and basic products as sustainability report in annual report is to reflect the level of accountability, responsibility and corporate transparency to investors and other stakeholders. The disclosure aims to establish good relationships and effective communication between the company, public and other stakeholders, regarding how the company has been integrating corporate social responsibility (CSR) to the social environment in every aspect of its operations. The purpose of this study was to determine the influence of corporate social responsibility (CSR) to the Return on Assets (ROA) and Return on Equity (ROE) as the dependent variable and Corporate Social Responsibility (CSR) as an independent variable in the food and beverage company in Indonesia which is listed on the Indonesia Stock Exchange (BEI) in 2012-2014. Population that studied in this research is all food and beverage companies for three periods, in 2012-2014 on the Stock Exchange, the sampling technique in this study using purposive sampling, the number of samples that meet the criteria in this study as many as 14 companies. data analysis Methods using simple linear regression analysis. The results of these studies show that the linear regression analysis showed that Corporate Social Responsibility (CSR) has a significant positive influence on the Return on Assets (ROA) and a significant positive effect on return on equity (ROE).